Translation, cross-cultural adaptation and validation of the composite physical function scale in Chinese community-dwelling older adults - Jiaying Qi; Jing Xu; Hui Zhang; Mingshuai Feng; Hongyan Meng; Li Wang (BMC Geriatrics)
Abstract Purpose To translate, cross-culturally adapt and validate the Composite Physical Function (CPF) scale in Chinese community-dwelling older adults. Methods The Chinese version of the CPF (C-CPF) was constructed by following Brislin’s guidelines. A cross-sectional study was conducted to evaluate the measurement properties of the C-CPF in 477 eligible older adults. Factor analysis, hypotheses testing, internal consistency and test-retest were performed to evaluate the validity and reliability of the C-CPF. Results The C-CPF was consistent with the original version, which consisted of a single dimension with 12 items. It had a Cronbach’s alpha coefficient of 0.901, fold-half reliability of 0.831 and test–retest reliability of 0.994. Structural validity was determined through exploratory factor analysis for a single-factor structure explained 75.391% of the total variance. Confirmatory factor analysis for a modified model provided an average fit index (chi-square/free ratio = 3.596, root mean square error of approximation = 0.099, normal fit index = 0.908, incremental fit index = 0.931, comparative fit index = 0.931 and Tucker–Lewis index = 0.909). Construct validity analysis revealed a significant difference in C-CPF scores amongst older adults in groups of different ages, regular exercise and physical activity habits (P < 0.01). Criterion validity was tested for the correlation between the results of C-CPF and the Senior Fitness Test (r = 0.446, P < 0.01). Conclusions The C-CPF scale serves as a valid and practical tool for widespread health screening to measure the level of comprehensive physical function and its decline amongst Chinese older adults. Further research is needed to explore the eligibility of the application of the C-CPF in a broad range of populations.